PENGARUH RETURN ON EQUITY, EARNING PER SHARE, INFLASI, DAN NILAI TUKAR TERHADAP HARGA SAHAM INDUSTRI PERTAMBANGAN DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Basilius Agung; Agus Solikhin; Moh. Ihsan (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the influence of Return on Equity, Earnings per Share, inflation, and exchange rates on the stock prices of mining sector companies listed on the Indonesia Stock Exchange during the 2018–2022 period. The study employs a quantitative approach using secondary data, specifically company financial statements and macroeconomic data. The sample was selected using purposive sampling, and data analysis was conducted using multiple linear regression. The results indicate that Return on Equity has a positive and significant effect on stock prices. Conversely, Earnings per Share, inflation, and exchange rates do not have a significant effect on stock prices. These findings suggest that a company's ability to generate profit from its own equity is a factor to which investors pay more attention than earnings per share indicators or macroeconomic conditions during the study period. Thus, Return on Equity emerges as the most significant variable in explaining stock price fluctuations for mining companies.